Hipotiroidisma pada Penderita Penyakit Graves Pasca Terapi Dengan Antitiroid : Laporan Kasus - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
Hypothyroidism in patient with Graves disease treated with antithyroid agent: A case report The paper presented a case of hypothyroidism in patient with Graves disease after have long been treated with antithyroid agent. The cause of hypothyroidism in this case might be (1) the effect of anti-thyroid agent, (2) natural history of Graves disease as a result of autoimmune mechanism, and (3) coincidental presentation of Graves disease and condition causes hypothyroidism (hashitoxicosis). A 39 year old woman, household , admitted to Sardjito Hospital because of general fatigue and facial edema. She was previously treated as Graves disease with PTU (propylthiouracil) 100 mg 3 times 100 mg/day for 2 years. Because of allergic reaction against PTU, the drug was replaced by NeomercazolÂ®. One year later the patient complaining body weight (BW) gain, with the laboratory investigation showed T3 = 0.78 Âµg/d1 (N: 0.6-1.9)